Can we rely on inflammatory biomarkers for the diagnosis and monitoring Crohn's disease activity? - Arieira, Cátia (2017)
Background: Small bowel capsule endoscopy (SBCE) is a very important tool in the diagnosis and monitoring of Crohn's disease (CD). The Lewis score (LS) and Capsule Endoscopy Crohn's Disease Activity Index (CECDAI) are used to quantify and standardize inflammatory activity observed in the SBCE. Aim: To evaluate the correlation between the LS and CECDAI scores and inflammation biomarkers (C-reactive protein [CRP] and erythrocyte sedimentation rate [ESR]). A secondary goal was to define thresholds for CECDAI based on thresholds already established for LS. Methods: This was a retrospective study of 110 patients with suspect or known CD, with involvement of small bowel. Linear regression was used to calculate thresholds of CECDAI corresponding to the thresholds already established for LS. A Pearson correlation (r) was used to calculate the correlation between the LS and CECDAI scores and biomarker levels. Only patients with exclusive involvement of the small bowel were selected (n = 78). Results: A moderate correlation was found between the endoscopic scores (r = 0.59, p < 0.001). CECDAI scores of 5.57 and 7.53 corresponded to scores of 135 and 790 in LS, respectively. There was a statistically significant correlation between CRP and the LS (r = 0.28, p = 0.014) and CECDAI (r = 0.29, p = 0.009). There was also a significant correlation between ESR and CECDAI (r = 0.29, p = 0.019), but not with LS. Conclusion: There is a moderate correlation between the two scores. This study allowed the calculation of thresholds for CECDAI based on those defined for LS. We found a weak correlation between SBCE endoscopic activity and inflammatory biomarkers.